Analysis of the factors that influence the reading habit of 8th grade students at liceo naval Guayaquil - Ramírez Rivera, Xavier Arturo (2018)
Education brings development; youth brings hope. That is the key to progress and success in society. Ecuador’s natural resources are not unlimited, and for this reason, the Ecuadorian government is trying to prepare the youth to face the challenges of tomorrow. In today’s society, the educational system has gone through many challenges in order to improve and provide a better academic preparation to our students. However, the task seems to be a difficult one and, to some extent, hopeless. Learning how to speak English by teaching reading is a result from a combination of factors, in general, students who are most at risk for reading and speaking are those who enter school with limited exposure to language and thus less prior knowledge of concepts related to phonemic sensitive, letter knowledge, print awareness, the purpose of reading, and general verbal skills, including vocabulary. Students raise in poverty with limited proficiency in English, students with limited proficiency and hearing impediments, and students from homes where the parents’ reading levels are low that increase risk of reading failure………….